Odourant reception in the malaria mosquito Anopheles gambiae - Carey, Allison (2010)
The mosquito Anopheles gambiae is the major vector of malaria in sub-Saharan Africa. It locates its human hosts primarily through olfaction, but little is known about the molecular basis of this process. Here we functionally characterize the Anopheles gambiae Odourant Receptor (AgOr) repertoire. We identify receptors that respond strongly to components of human odour and that may act in the process of human recognition. Some of these receptors are narrowly tuned, and some salient odourants elicit strong responses from only one or a few receptors, suggesting a central role for specific transmission channels in human host-seeking behavior. This analysis of the Anopheles gambiae receptors permits a comparison with the corresponding Drosophila melanogaster odourant receptor repertoire. We find that odourants are differentially encoded by the two species in ways consistent with their ecological needs. Our analysis of the Anopheles gambiae repertoire identifies receptors that may be useful targets for controlling the transmission of malaria.